The Correlation Between IL-1Î² and IL-10 Levels in Estimating The Risk of Febrile Seizures - Andi Gunawan; M Muid; Hidayat Suyudi; Barlianto wisnu; Krisni Subandiyah (Journal of Tropical Life Science, 2014)
Febrile seizures are the most common forms of seizures in children with fever. A data from clinical and experimental studies suggest the potential role of immune generate products in their genesis. The balance between proinflammatory (IL-1Î²) and anti-inflammatory (IL-10) cytokines influences the regulation of infections and plays a role in the pathogenesis of febrile seizures. In existing literature, there is no research on the correlation between IL-1Î² and IL-10 levels as well as the ratio of IL-1Î² to IL-10 in estimating the risk of febrile seizures in seizure prone children aged between 3 months and 5 years. In this study, IL-1Î², IL-10 levels and ratio of IL-1Î² to IL-10 in the risk of febrile seizures were investigated, and respondents were divided into three groups: febrile seizures, febrile without seizures and healthy children without histories of febrile seizure. This study has used A cross-sectional design, and each group had 17 co-respondents. IL-1Î² and IL-10 levels were measured by ELISA. Data were analyzed by SPSS 15. Findings showed there were significant differences between IL-1Î² and IL-10 as well as in the ratio of IL-1Î² to IL-10 between febrile seizure patients and healthy children. It was concluded that there were significant correlations between IL-1Î² and IL-10 levels as well as IL-1Î² to IL-10 ratios in estimating the risk of febrile seizures.